Sadfishing as Emotional Disclosure in the Bipolar Hashtag on TikTok - Fathiyyah Azizah (INJECT (Interdisciplinary Journal of Communication), 2026)
Public discourse often dismisses "sadfishing" as manipulative attention-seeking, risking the delegitimization of genuine psychological distress. This issue is compounded by TikTok’s algorithmic recommendation system, which privileges high-intensity emotional content, transforming private distress into public viral narratives regardless of creator intent. This study aims to explore how individuals with bipolar disorder experience and interpret their emotional disclosures within the #bipolar hashtag community on TikTok. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with two key TikTok content creators and supplemented by non-participant digital observation of three supporting informants. The analysis followed the Miles and Huberman framework, comprising data condensation, data display, and conclusion drawing to ensure analytical rigor. Results indicate that creators utilize the #bipolar hashtag to contextualize emotional states within a clinical identity framework, viewing their posts as legitimate coping mechanisms or cries for help. However, the findings reveal a significant tension caused by algorithmic visibility; emotionally vulnerable content is often amplified to unintended audiences, leading to fragmented responses. While survivors of similar conditions offer empathy and validation, others dismiss these disclosures as "sadfishing," utilizing the term as an external label to delegitimize genuine psychological distress. This study concludes that sadfishing is not a singular behavioral motive, but an interpretively constructed phenomenon mediated by platform affordances, norms, and mental health literacy. Digital vulnerability is a relational process where audience interpretation and platform infrastructures collectively define the perceived authenticity of disclosed emotions.